Aunthentic Leadership - Aura Bahrul Safitri; Atika Kharisma Putri; Farid Al Farizi; Mochammad Isa (Jurnal Manajemen Kreatif dan Inovasi, 2023)
The study of leadership includes autnetic leadership. This focuses on the genuineness and authenticity of authentic leadership. Authentic leadership is about authentic leaders and their leadership, as described in this method. In order to understand what authentic leadership is, authentic approaches, authentic components, and authentic variables must first be identified. Although the information used in this study is secondary. Secondary data is information that researchers have gleaned from pre-existing sources or from the findings of studies and documents that have been preserved as research artifacts. The conduct of leaders and followers is positively impacted by authentic leadership style. Although it can happen, genuine development is difficult to construct